2011
DOI: 10.1080/0965254x.2011.581383
|View full text |Cite
|
Sign up to set email alerts
|

Digital marketing strategies that Millennials find appealing, motivating, or just annoying

Abstract: With the increasing usage of digital media by consumers, more companies are using digital marketing to reach their target markets. The purpose of this study is to examine various marketing strategies that are commonly used in digital media and ascertain which ones are preferred by Millennials and are effective in influencing behavior. Millennials have been identified as a driving force behind online shopping. While there have been numerous studies about online advertising, there has been little academic resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
19

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 26 publications
(16 reference statements)
4
141
0
19
Order By: Relevance
“…Having grown up socializing and shopping online, the use of this e-commerce generation will continue to grow along with their discretionary income. Although millennials do not like pop-up publicity, the graphics are very effective at capturing their attention and will repeatedly visit a website that has competitive pricing and good shipping rates (Smith, 2011).…”
Section: The Millennial Consumer Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Having grown up socializing and shopping online, the use of this e-commerce generation will continue to grow along with their discretionary income. Although millennials do not like pop-up publicity, the graphics are very effective at capturing their attention and will repeatedly visit a website that has competitive pricing and good shipping rates (Smith, 2011).…”
Section: The Millennial Consumer Behaviormentioning
confidence: 99%
“…Martin (2015) (2015) Rahman (2015), Weyland (2011), Bilgihan (2016. Processing variable Psychological aspects Martin (2015), Smith (2011), Satinover N. et al (2015, Valentine & Powers (2013), Junker et al (2016), Muda et al (2016), Ordun (2015), , , Weyland (2011), Francis & Burgess (2015), Weber (2015), Bilgihan (2016).…”
Section: Ijmsccsenetorg International Journal Of Marketing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Millennials are highly influenced by social media in many ways (Martin &Turley, 2004) and are affected by online reviews more than other generation (Smith, 2012). Some studies showed that millennials are the first generation to give a greater importance to online word of mouth (information shared on SM) than to traditional types of recommendations or advertising tools (Senecal & Nantel, 2004;Smith, 2011). Thus, as Pate and Adam (2013) found out, millennials are more likely to acquire a product that was "liked" or recommended by their friends on SM and they perceive comments as more "transparent" and blogs "more objective".…”
Section: Millennials and Social Mediamentioning
confidence: 99%
“…Traditional advertising does not have the same effect on Millennials as on previous generations (Valentine & Powers, 2013;Young, 2015) because of their reluctance to use anything that is "not digital", and the fact that the online environment is more trustworthy and provides them with greater information safety (Neuborne, 1999;Valentine & Powers, 2013;Young, 2015). Millennials prefer advertising spots and clips broadcast on YouTube and other video channels, the in-game advertising and the popup ads on the accessed web pages (Taken Smith, 2011;Young, 2015).…”
Section: Millennials and Social Media Communicationmentioning
confidence: 99%